2015
DOI: 10.3389/fncel.2015.00428
|View full text |Cite
|
Sign up to set email alerts
|

T-type calcium channels cause bursts of spikes in motor but not sensory thalamic neurons during mimicry of natural patterns of synaptic input

Abstract: Although neurons within intact nervous systems can be classified as ‘sensory’ or ‘motor,’ it is not known whether there is any general distinction between sensory and motor neurons at the cellular or molecular levels. Here, we extend and test a theory according to which activation of certain subtypes of voltage-gated ion channel (VGC) generate patterns of spikes in neurons of motor systems, whereas VGC are proposed to counteract patterns in sensory neurons. We previously reported experimental evidence for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 87 publications
(174 reference statements)
0
7
0
Order By: Relevance
“…4g). MD neurons in vitro have a bimodal resting membrane potential distribution 37 , suggesting different degrees of excitability. Because our analysis suggested that two MD populations are driven by different degrees of cortical engagement ( Supplementary Fig.…”
Section: Neurons Regulate Pfc Representational Switching Likely Thmentioning
confidence: 99%
“…4g). MD neurons in vitro have a bimodal resting membrane potential distribution 37 , suggesting different degrees of excitability. Because our analysis suggested that two MD populations are driven by different degrees of cortical engagement ( Supplementary Fig.…”
Section: Neurons Regulate Pfc Representational Switching Likely Thmentioning
confidence: 99%
“…Adaptation had a more striking effect on burst firing and synchronous evoked spikes. Bursts -groups of spikes with very short inter-spike intervals made possible by the de-inactivation of T-type calcium channels (Kim et al, 2015;S. Suzuki & Rogawski, 1989) -have been shown to provide potent synaptic drive to S1 (Sherman, 2001;Swadlow, 2002;Swadlow & Gusev, 2001), and may therefore be critical for shaping cortical sensory responses.…”
Section: Adaptation Primarily Influences Feature Response Timing In Vmentioning
confidence: 99%
“…For example, the theory correctly predicted the experimental observation that T-type calcium channels are homoeostatic in counterbalancing opponent IPSG in thalamocortical neurons of LGN 50 . The more general theory proposes differences between sensory and motor neurons, and it correctly predicted evidence that T-type calcium channels are not homoeostatic but cause bursts of spikes in motor thalamus 51 . In addition to predicting the properties of a type of neuron, theory may also be useful in explaining variability in ion channel parameters across neurons of the same type, particularly by indicating which combinations of ion channel parameters work in a concerted manner to maintain near optimal homoeostatic excitability 60 61 .…”
Section: Discussionmentioning
confidence: 84%
“…Together with recent experiments 50 51 , we have tested a theory of the information contributed to membrane voltage by synapses and ion channels 21 40 52 53 . The theory extends a long line of research relating neuronal function to quantitative principles of information 23 24 .…”
Section: Discussionmentioning
confidence: 99%